2007
DOI: 10.1002/jez.b.21204
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenic machines evolve more rapidly than the signals that pattern them: lessons from amphibians

Abstract: The induction of mesoderm and the patterning of its dorsal-ventral and anterior-posterior axes seems to be relatively conserved throughout the chordates, as do the morphogenic movements that produce a phylotypic stage embryo. What is not conserved is the initial embryonic architecture of the fertilized egg, and the specific cell behaviors used to drive mesoderm morphogenesis. How then do conserved patterning pathways adapt to diverse architectures and where do they diverge to direct the different cell behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 205 publications
0
17
0
Order By: Relevance
“…Lastly, on the tissue scale the classical processes of secondary induction may serve to signal the success of a particular tissue movement or elicit further morphogenetic movements. The molecular and cellular scale processes that provide feedback from the mechanical processes of morphogenesis are poorly understood and their resolution will provide deeper insights into many larger questions in evolution as well as the nature of disease liability and birth defects 42,9597 .…”
Section: Mechanics Feedback and Robust Programs Of Developmentmentioning
confidence: 99%
“…Lastly, on the tissue scale the classical processes of secondary induction may serve to signal the success of a particular tissue movement or elicit further morphogenetic movements. The molecular and cellular scale processes that provide feedback from the mechanical processes of morphogenesis are poorly understood and their resolution will provide deeper insights into many larger questions in evolution as well as the nature of disease liability and birth defects 42,9597 .…”
Section: Mechanics Feedback and Robust Programs Of Developmentmentioning
confidence: 99%
“…Thus, it is likely that the spatial distribution of the cells that receive these signals depends on how morphogenetic mechanisms move them, and on how they move and deform the signalling territories (thus affecting, over time, the spatial distribution of the cells that receive a signal). As such, vertebrate gastrulation probably uses strong morphodynamic mechanisms (Shook and Keller, 2008).…”
Section: Type E: Vertebratesmentioning
confidence: 99%
“…Except for mammals, this variation seems to involve, mainly, the amount of yolk. This does not necessarily have dramatic effects on adult morphology (del Pino and Elinson, 1983;del Pino, 1989;del Pino and Loor-Vela, 1990), although the morphogenetic movements involved can be quite different (Shook and Keller, 2008).…”
Section: Type E: Vertebratesmentioning
confidence: 99%
“…Although all pattern transformations in development can be said to be done by developmental mechanisms a specifi c pattern transformation can be equally realisable by different developmental mechanisms. Indeed, it has been extensively shown that different developmental mechanisms underlie very similar morphologies in different species (Müller 2007;Shook and Keller 2008) or even in the same individual (Catala et al 1995). On the other hand a developmental mechanism does not always produce the same pattern transformation.…”
Section: Variational Propertiesmentioning
confidence: 98%